2022
DOI: 10.1021/acsanm.2c02320
|View full text |Cite
|
Sign up to set email alerts
|

Gold–Silver Bimetallic Nanoclusters Protected by Glutathione S-Transferase for Colorimetric Sensing of Oxytetracycline

Abstract: Gold−silver alloy nanoclusters (AuAgNCs) were synthesized, protected by glutathione S-transferase (GST). The asprepared GST-AuAgNCs displayed strong (QY = 15.9%) fluorescence with two emission peaks around 477 and 653 nm under excitation of 395 nm. In this system, both the NC core and the organic shell contributed to the development of a "turn-on" ratiometric fluorescent probe for sensitively and selectively detecting oxytetracycline (OTC). First, the green fluorescence at 477 nm enhanced with the addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…18). 184 This is due to the reduction of Ag( i ) in B7 's shell structure into Ag(0), and the aggregation of B7 with OTC, which triggers AIE. Consequently, green fluorescence at 477 nm was enhanced over red fluorescence at 653 nm.…”
Section: Sensing Of Drug Moleculesmentioning
confidence: 99%
“…18). 184 This is due to the reduction of Ag( i ) in B7 's shell structure into Ag(0), and the aggregation of B7 with OTC, which triggers AIE. Consequently, green fluorescence at 477 nm was enhanced over red fluorescence at 653 nm.…”
Section: Sensing Of Drug Moleculesmentioning
confidence: 99%
“…The oxytetracycline molecules could decrease the emission at 477 nm but have no apparent effect on emission at 653 nm. This double wavelength emission system is desirable and used in ratiometric detection of the target drug …”
Section: Metal Ncsmentioning
confidence: 99%
“…This double wavelength emission system is desirable and used in ratiometric detection of the target drug. 546 In addition to the luminescence benefits of bimetallic NCs, combining two atoms is also used for designing other biosensors. 547,548 It has been reported that integrating gold atoms into other NCs can enhance their adsorption ability on the electrode surfaces and improve their stability, detection sensitivity, and charge-transferring ability, which are great benefits in designing electrochemical biosensors.…”
Section: Dopping and Alloying Of Ncs For Diagnosticsmentioning
confidence: 99%
“…GST containing tryptophan and tyrosine residues can serve to reduce high-valence metal ions, promoting the fabrication of CuNCs through metal-GST coordination bonds. 27,28 The obtained GST-CuNCs exhibited blue uorescent emission at 400 nm when excited at 325 nm. Meanwhile, the products exhibited exceptional stability under different conditions.…”
Section: Introductionmentioning
confidence: 99%